Novel Endoscopic Stent for Anastomotic Leaks after Total Gastrectomy Using an Anchoring Thread and Fully Covering Thick Membrane: Prevention of Embedding and Migration - Jung, Gum Mo; Lee, Seung Hyun; Myung, Dae Seong; Lee, Wan Sik; Joo, Young Eun; Jung, Mi Ran; Ryu, Seong Yeob; Park, Young Kyu; Cho, Sung Bum (Journal of gastric cancer, 2018)
The endoscopic management of a fully covered self-expandable metal stent (SEMS) has been suggested for the primary treatment of patients with anastomotic leaks after total gastrectomy. Embedded stents due to tissue ingrowth and migration are the main obstacles in endoscopic stent management. The effectiveness and safety of endoscopic management were evaluated for anastomotic leaks when using a benign fully covered SEMS with an anchoring thread and thick silicone covering the membrane to prevent stent embedding and migration. We retrospectively reviewed the data of 14 consecutive patients with gastric cancer and anastomotic leaks after total gastrectomy treated from January 2009 to December 2016. The technical success rate of endoscopic stent replacement was 100%, and the rate of complete leaks closure was 85.7% (n=12). The mean size of leaks was 13.1 mm (range, 3-30 mm). The time interval from operation to stent replacement was 10.7 days (range, 3-35 days) and the interval from stent replacement to extraction was 32.3 days (range, 18-49 days). The complication rate was 14.1%, and included a single jejunal ulcer and delayed stricture at the site of leakage. No embedded stent or migration occurred. Two patients died due to progression of pneumonia and septic shock 2 weeks after stent replacement. A benign fully covered SEMS with an anchoring thread and thick membrane is an effective and safe stent in patients with anastomotic leaks after total gastrectomy. The novelty of this stent is that it provides complete prevention of stent migration and embedding, compared with conventional fully covered SEMS.